Virtual Reality Therapy as an Innovative Intervention in Mental Health: A Literature Review - Afra Ruchudinia Mufida; Aisyah Adinda Kurniawan; Diska Aprisa Lestari; Eprel Pranacinsa Tanagan; Azizatul Adni (Lombok Medical Journal, 2026)
The advancement of digital technology has driven innovation in mental health interventions, including Virtual Reality Therapy (VRT), a technology-based approach that enables patients to experience immersive and controlled three-dimensional environments. This literature review aims to examine the concepts and effectiveness of VRT in managing mental health disorders. The findings indicate that VRT is effective in reducing symptoms of anxiety, depression, post-traumatic stress disorder (PTSD), and substance use disorders. It is commonly integrated with exposure therapy and cognitive behavioral therapy (CBT), allowing gradual and controlled exposure to anxiety-provoking stimuli in a safe environment. In addition, VRT enhances patient engagement and improves accessibility of mental health services, including through smartphone-based applications. However, several limitations remain, particularly related to methodological variability and the lack of long-term evidence. Therefore, further research is needed to evaluate long-term outcomes and optimize its implementation in clinical practice. In conclusion, VRT represents a promising and innovative intervention that can serve as both an alternative and complementary approach in mental health care